Odpowiedzi

2009-10-04T20:59:52+02:00
A)6+7*1/2= 6 + 7/2= 9 i 1/2
b)-6*(-6) : (9)= -6*(-2/3)= 4
c)-3*(-12)-5/7-9=36-5/7-9=36-5/7-8 7/7= 36-8 2/7=35 7/7- 8 2/7= 27 5/7
d)nie jestem do końca pewna
2009-10-04T21:06:47+02:00
A) 6-(-7)x(-2)/-4 = 6 - 14/-4 = 6 - 3,5 = 2,5

b) (-2-4)x(-6):(-3)²= -6 * -6 : 9 = 36 : 9 = 4

c) (-3)x(-2-10)-5/7-9= -3 * -12 - 5/7 - 9 = 36 - 5/7 - 9 = 35²/₇ - 9 = 26²/₇

d) 15-(-2)x4/-11+4 + 5-2/2-3= 15 - 8/11 + 5 - 2/2 - 3 = 15 - 4³/₁₁ - 2/2 - 3 = 10⁸/₁₁ - 2/2 - 3 = 9⁸/₁₁ - 3 = 6⁸/₁₁
2009-10-04T21:09:35+02:00
D) 15-(-2)*4/-11+4+5-2/2-3=
15+2*4/-11+4+5-1-3=
17*4/-11+5=
17/1*4/-11+5=68/-11+5=68/-11+55/11=13/-11=1i 2/-11